The long weekend : [large type] a novel - Macmillan, Gilly (Harper Large Print, an imprint of HarperCollinsPublishers, 2022)
By the time you read this, I'll have killed one of your husbands. In an isolated retreat, deep in the Northumbria moors, three women arrive for a weekend getaway. Their husbands will be joining them in the morning. Or so they think. But when they get to Dark Fell Barn, the women find a devastating note that claims one of their husbands has been murdered. Their phones are out of range. There's no internet. They're stranded. And a storm's coming in. Friendships fracture and the situation spins out of control as each wife tries to find out what's going on, who is responsible and which husband has been targeted. This was a tight-knit group. They've survived a lot. But they won't weather this. Because someone has decided that enough is enough. That it's time for a reckoning.